Autologous hematopoietic stem cell transplantation in elderly patients (≥ 70 years) with non-Hodgkin's lymphoma: A French Society of Bone Marrow Transplantation and Cellular Therapy retrospective study. Issue 5 (September 2015) - Hermet, E.; Cabrespine, A.; Guièze, R.; Garnier, A.; Tempescul, A.; Lenain, P.; Bouabdallah, R.; Vilque, J.P.; Frayfer, J.; Bordessoule, D.; Sibon, D.; Janvier, M.; et al.
Abstract: Introduction: Limited data is available on the feasibility of high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (AHSCT) in elderly patients over 70 years of age with non-Hodgkin's lymphoma (NHL). Materials and Methods: In the setting of the Société Française de Greffe de Moelle et de Thérapie Cellulaire (SFGM-TC) group, we retrospectively analyzed 81 consecutive patients with NHL over 70 years of age who received AHSCT. Results: The median age at AHSCT was 72.3 years [70–80]. Patients' were diagnosed with diffuse large B-cell lymphoma (n = 40), follicular lymphoma (n = 16), mantle cell lymphoma (n = 15), T-cell lymphoma (n = 5), and other (n = 5). Hematopoietic Cell Transplantation Comorbidity Index (HCT-CI) was 0 in 73% of patients. Main conditionings were BEAM (Carmustine-Etoposide-Cytarabine-Melphalan, n = 61) and melphalan alone (n = 14). Median delays to reach 0.5 × 10 9 /L neutrophils and 20 × 10 9 /L platelets were of 12 [9–76] days and 12 [0–143] days, respectively. One hundred day and one year cumulative incidence of NRM was 5.4% and 8.5%, respectively. The main cause of death remains relapse. Conclusion: In conclusion, this study revealed that AHSCT seemed to be acceptable in patients over 70 years of age with NHL. Patient age is not a limiting factor if clinical condition is adequate.